2020
DOI: 10.3390/polym12010224
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Drop Impact Energy and Residual Compressive Strength According to the Lamination of CFRP with EVA Sheets

Abstract: Carbon-fiber-reinforced plastic is an important building material; however, its application is limited because of its brittleness, leading to vulnerability under shock. Thus, the strength performance of carbon-fiber-reinforced plastics needs to be improved. Here, the drop impact test was conducted to analyze the impact energy and fracture characteristics of carbon-fiber-reinforced plastics and ethylene vinyl acetate sheets. The compression after impact test was performed to assess the residual compressive stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Compared to other polyethylene resins, EVA is more flexible and very similar to rubber [ 68 ]. Moreover, this copolymer presents good adhesion to an extensive range of materials, like ceramics, metals, and other polymers [ 76 , 77 ].…”
Section: Mouthguard Base Materialsmentioning
confidence: 99%
“…Compared to other polyethylene resins, EVA is more flexible and very similar to rubber [ 68 ]. Moreover, this copolymer presents good adhesion to an extensive range of materials, like ceramics, metals, and other polymers [ 76 , 77 ].…”
Section: Mouthguard Base Materialsmentioning
confidence: 99%
“…In previous studies, the drop-weight impact failure trend of polymer materials has been found to occur through either the matrix cracking damage of the single layer, which is internal damage; or delamination from the interface; or the external damage. Thus, there exist three cases of failure mode in composite due to drop-weight impact [ 13 , 21 , 23 ]. Those cases are puncture failure mode, crack failure mode, and brittle fracture mode.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the brittle fracture mode (B-mode), failure occurs with radial crack propagation from the center of the specimen. Moreover, this failure behavior is observed in polystyrene, and the brittle failure mode has slight influence on the absorption energy [ 13 , 15 , 16 , 17 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The experimental results showed that the basalt hybrid system had a high impact energy and peak load compared to the flax/VE composite without hybridisation, indicating that a hybrid approach is a promising strategy for enhancing the toughness properties of natural fibre composites. The πCT and SEM images revealed that the failure modes observed for flax and flax basalt hybrid composites were a combination of matrix cracking, delamination, fibre breakage, and fibre pull out.Polymers 2020, 12, 806 2 of 18 Among the natural fibres used in polymeric composites, bast fibres (flax, hemp, jute, and kenaf) stand out as the most promising reinforcements [9,10]. Due to their unique hollow structure, these fibres provide a good damping property, which is very important when it comes to dealing with impact damage and vibration damping behaviours.…”
mentioning
confidence: 99%
“…Polymers 2020, 12, 806 2 of 18 Among the natural fibres used in polymeric composites, bast fibres (flax, hemp, jute, and kenaf) stand out as the most promising reinforcements [9,10]. Due to their unique hollow structure, these fibres provide a good damping property, which is very important when it comes to dealing with impact damage and vibration damping behaviours.…”
mentioning
confidence: 99%